Innovative trend analysis of rainfall and temperature over Nubra Valley, Ladakh - AMBRISH; VIRENDER SINGH NEGI; YUVRAJ SINGH RATHORE; BINDHY WASINI PANDEY (Journal of Agrometeorology)
Climate change impacts on mountains have increased over the past few decades, with evident and significant consequences for people and ecosystems. This study investigates the long-term trend in rainfall and temperature (1951-2022) over Nubra Valley, Ladakh, India employing the Innovative Trend Analysis (ITA) using IMD gridded (0.25 x 0.25) rainfall and (1.0 x 1.0) temperature data. The results of ITA indicate no trend in May for 70% of areas, in November in south-western part, and in December in northern parts of the valley. A notable trend only in November in selected areas of central and northern part of the valley. Most of the months showed a rising pattern in rainfall. The tmin trend reveals an increasing trend in months, except for no trend in January and October in the southern region; there is a significant decreasing trend in February and July in the southern region. The tmax trend even shows an increasing trend, excluding June, displaying a significant decreasing trend. January and October in the eastern region and November in the western show no trend. The results are indicative of a rising rainfall and temperature trend in the Nubra Valley.